Adherence challenges to therapeutic footwear among high risk diabetic foot populations in urban Southwest China - Wangqiao Zhu; Liuxue Lu; Lifang Huang; Sulan Long; Lina Ou; Meng Yang; Yongxian Wei; Yanfang Lu; Yunjiao Tang; Jia Liu (Scientific Reports)
Abstract Diabetic foot ulcers [DFUs] are severe complications of diabetes, and therapeutic footwear plays a crucial role in their prevention. However the factors influencing adherence to therapeutic among high-risk individuals in urban areas remain poorly understood. With increasing urbanization and migrant workers, this study aims to explore the challenges of adherence to therapeutic footwear among high-risk diabetic foot patients in urban area. This study employed a qualitative descriptive design. Data were collected through semi-structured interviews and focus group discussions, and analyzed using a thematic approach. A total of 25 participants (20 patients and 5 healthcare providers) were recruited through purposive sampling. Two key challenges of footwear adherence were identified: (1) inadequacy of consistent and reliable health resources, and (2) appearance-related barriers to footwear adherence: professionalism, fashion, and social perception. Participants reported inconsistent and unreliable health information, including confusion from online sources and varied hospital guidance, which reduced their confidence in wearing therapeutic footwear. Additionally, appearance-related barriers—such as workplace dress codes, fashion preferences, and fear of social judgment—discouraged use of therapeutic footwear in both professional and social settings. This study highlights the need to integrate social and functional elements into the design of therapeutic footwear. Nursing professionals play a critical role in enhancing communication and coordination around foot care. Enhancing access to reliable health information is essential for promoting DFU prevention, particularly among urban migrant populations.